Improving Air Quality in Urban Areas by Enhancing Walking to School Programs: Addressing Mode Choice Barriers and Optimizing Walking Distance for Elementary School Students - Widjajanti, Endang (Journal of Ecohumanism, 2024)
The purpose of this study is to determine the improvement in air quality that can occur if a walking-to-school program is implemented for elementary school students in the city of Depok. This research analyzes the transportation modes used by elementary school students to and from school in urban areas and the distance from their homes to school if they swalk. The study was conducted on students at SD Negeri Pasir Putih 03, Sawangan, Depok, to serve as a basis for programs aimed at encouraging students to walk to school. Data collection was carried out through field observations and interviews using a questionnaire via Google Forms, covering age, grade, address, departure and arrival times at school, modes of transportation used, and reasons for using them. Descriptive statistical methods were used to determine the walking distances of elementary school students by age. The most commonly chosen transportation mode for commuting to and from school was motorcycles (61.42%), followed by walking (29.96%). The rest used bicycles (2.80%) and a combination of walking and cycling. The analysis of walking distances for ages 6-13 showed that at the 50% cumulative percentage, the distance was less than or equal to 328 meters, with the shortest distance being 50 meters and the longest being 800 meters. Implementing a walking-to-school program for distances up to 100 meters is highly appropriate, as it not only improves students’ health but also enhances air quality by reducing CO emissions during school hours. The estimated reduction in CO emissions with a moderate scenario during 1 hour in the morning along the distance between the gathering point and the school (100 meters) in Depok city is 431 grams/day or equivalent to 87 kg/year.